2009
DOI: 10.1007/s12011-009-8530-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Cell Wall and Lignifying Enzymes Modulations in Bean Roots in Response to Copper Stress

Abstract: Fourteen-day-old bean seedlings were cultured in nutrient solution containing Cu(2+) ions at various concentrations (50 and 75 microM of CuSO(4)) for 3 days. This excess of copper induced a reduction in the water volume absorbed by the plants. Moreover, this reduction was accompanied by an increase of the amount of copper taken up by the roots. Analysis by native gel electrophoresis of cell wall peroxidase activities in the roots revealed a stimulation of two anionic isoforms (A(2) and A(3)) under cupric stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…410 nm, in culture), and consists of only three well-differentiated layers . In other studies, cell-wall thickening was commonly observed in vascular plants and mosses exposed to HMs (Krzeslowska et al, 2009;Bouazizi et al, 2010;Yu et al, 2011). This response was associated with increased amounts of polysaccharides in the cell walls (Wierzbicka, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…410 nm, in culture), and consists of only three well-differentiated layers . In other studies, cell-wall thickening was commonly observed in vascular plants and mosses exposed to HMs (Krzeslowska et al, 2009;Bouazizi et al, 2010;Yu et al, 2011). This response was associated with increased amounts of polysaccharides in the cell walls (Wierzbicka, 1998).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, excess copper induces changes in the oxidant state indicated by over-production of H 2 O 2 . This radical has been detected in the intercellular spaces and in the cell walls of leaves from copper-treated bean plants [6]. Copper can for example act through changes in H 2 O 2 -dependent peroxidase activity leading to cell wall stiffening due to the formation of cross-links between lignin molecules [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These changes were proposed to represent a structural response of the plants to cupric stress that may prevent further uptake of the ion [6]. The observed structural changes were accompanied by changes in the abundance of metabolites and in the activity of enzymes involved in cell wall metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Still increased GPO activity in roots indicated an injury there since stress damage at the tissue, ultrastructural or functional level is a prerequisite for peroxidase induction (Edreva 1991). Roots, exposed directly to elevated Cu concentrations accumulate it and serve as a first barrier to its transport toward the shoots Bouazizi et al 2010). As we found earlier the 150Cu treatment brought about a fourfold increase in root Cu content, while the increase in shoots was only 65%.…”
Section: Separate Effect Of Excess Coppermentioning
confidence: 99%
“…They speculated that the latter might be induced by increased rigidity of the cell wall to seriously impact permeability and nutrient uptake. Cell wall stiffening through enhanced cross-linking of lignin monomers with the contribution of peroxidase might be a structural defense against metal stress to reduce the uncontrolled influx of copper (Bouazizi et al 2010). The changes in root GPO were not concentration dependent, but this has been the case in other studies too (Zhao et al 2010).…”
Section: Separate Effect Of Excess Coppermentioning
confidence: 99%